Trabajo global y desigualdades en el mercado laboral. - Castillo Fernández, Dídimo; Baca Tavira, Norma; Todaro Cavallero, Rosalba (CLACSO, 2016)
Neoliberal globalization fostered a paradoxical tension between the supposed tendencies towards social homogenization and standardization, and the appearance of new social inequalities. Today's society, far from experiencing the consequences of the so-called "end of work", expresses its effects in terms of the forms of labor management promoted, flexibility, deregulation of labor relations and the loss of quality of occupations. In this environment , it is even contradictory that the concepts of employment and unemployment have lost their classic meanings in the face of the increase in socially unprotected and precarious salaried work, the disappearance of conventional salary modalities, the expansion of independent, autonomous or self-employed work, and the emergency of increasingly heterogeneous and unequally profitable occupations that affect a large part of the workforce, in particular the socially and demographically most vulnerable, giving rise to new forms of social inequality and poverty.